The fluorine in the prevention of decay in the temporary teething. Fluorated varnishes. - Perales Zamora, Segundo (2006)
Since 1950, the investigations of Cox, Dean and Armstrong Iead to conclude that fluoride increased the resistance to dental caries but produced fluorosis in high concentrations (over 1 ppm ). Nowadays, in spite of the varied lines of research based in caries prevention methods, none of them has overcome Fluoride as a cheap, inoffensive and efficient method for this purpose. A review about FIuoride as an Early Childhood Dental Caries preventive method is presented, focused in fluoride varnishes. We also show the scheme of Fluoride application.